VARIABEL-VARIABEL YANG MEMENGARUHI KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) MASYARAKAT BIDARACINA JATINEGARA JAKARTA TIMUR - Ladiyance, Selfia; Yuliana, Lia (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
River pollution negatively impact on water used as supporting domestic needs, environmental health and economic activity. Economic losses due to river pollution associated with economic valuation. The purpose of this study is: (1) calculate the value of Willingness To Pay (WTP) and the total value of WTP, (2) analyze the variables that influence the willingness to pay Bidaracina. The analysis used is the Contingent Valuation Method (CVM) and logistic regression. The results showed that: (1) The amount of WTP value is Rp 4.325,00 per month and the total value of WTP is Rp 1.935.576,92 per month , (2) variables that affect the willingness to pay Bidaracina is knowledge of river pollution, home ownership status, education and household income last. Advice can be given: (1) the results of the estimated WTP values can be used for the preservation of the Ciliwung River. (2) needs to be an increase in extension activities and dissemination of information on pollution of the Ciliwung River.